PENINGKATKAN KESETARAAN GENDER DI UKRAINA (OLEH UN WOMEN) - NOVIYANTI SOLEMAN; Rifki Elindawati (AL-WARDAH: Jurnal Kajian Perempuan, Gender dan Agama, 2019)
Ukraine is one of the UN members which had ratified the convention of elimination discrimination against women during 1979. This is followed by the significant number of discrimination against women, because of political and economic instability. In addition, the situation has been getting worse due to crimea annexation and millitary crisis. Thus, UN Women as the part of UN agencies for advancing gender equality takes action to support in eradicating women discrimination in Ukraine. To asses those condition, this research aims to analyze efforts of UN Women towards the issue, based on theory of the role of international organization by Cliver Archer.